BiFeO3-based high-entropy energy storage ceramic material with wide-temperature stability as well as preparation method and application of BiFeO3-based high-entropy energy storage ceramic material

By combining high entropy engineering with liquid phase sintering, BiFeO3-based high entropy energy storage ceramics with high breakdown strength and high energy storage density were prepared, which solved the hysteresis problem of traditional dielectric materials and the problem of Bi volatilization during high-temperature sintering of BiFeO3-based ceramics, and achieved wide temperature stability and high-efficiency energy storage performance.

CN120757373APending Publication Date: 2025-10-10SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510789922.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The inherent properties of traditional dielectric materials, such as the strong hysteresis of ferroelectrics and antiferroelectrics, limit the realization of large polarization difference and energy storage performance. The volatilization of Bi during high-temperature sintering of BiFeO3-based ceramics leads to high leakage current and low breakdown strength, making it difficult to maintain a moderate polarization difference while improving the breakdown strength.

Method used

A synergistic optimization strategy combining high entropy engineering and liquid phase sintering is adopted. By introducing a high entropy system to destroy the long-range ferroelectric order and introducing a low-melting-point sintering aid BaCu(B2O5), the densification sintering of ceramics is achieved at low temperature, Bi volatilization is inhibited, and the formation of nano-polarized regions and grain refinement are promoted.

Benefits of technology

The preparation of BiFeO3-based high-entropy energy storage ceramic materials with high breakdown strength and high energy storage density has been achieved. It has excellent high-temperature stability and an ultra-wide temperature operation window, which significantly improves energy storage performance, reduces energy consumption and reduces Bi volatilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757373A_ABST
    Figure CN120757373A_ABST
Patent Text Reader

Abstract

The invention discloses a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability as well as a preparation method and application of the BiFeO3-based high-entropy energy storage ceramic material. The stoichiometric formula is (1-x) (0.67 BiFeO3-0.33 BaTiO3)-x (Na0. 2Bi0. 2Ba0. 2Sr0. 2Ca0. 2) (Ti0. 8Zr0. 2) O3, x represents molar percentage and is 0.06-0.15, the ceramic material realizes synergistic enhancement of polarization difference (delta P) and breakdown strength (Eb), the ceramic with high breakdown strength, high energy storage density and excellent high-temperature stability (83-459 DEG C) is obtained, and compared with other Bi-based materials, the temperature change range is + / -15% and is higher than 400 DEG C, and the temperature change range is larger than or equal to 90 DEG C. The invention also discloses a preparation method of the ceramic material. The material is expected to be used in practical applications simultaneously requiring high temperature, high pressure and high energy storage; in another scheme, the raw materials of the ceramic material comprise (1-x) (0.67 BiFeO3-0.33 BaTiO3)-x (Na < 0.2 > Bi < 0.2 > Ba < 0.2 > Sr < 0.2 > Ca < 0.2 >) (Ti < 0.8 > Zr < 0.2 >) O3 and 0.5-2wt% of BaCu (B2O5), x represents the molar percentage and is 0.06-0.15, and x represents the molar percentage. By designing a collaborative optimization strategy combining high-entropy engineering and liquid-phase sintering and introducing BaCu (B2O5), the sintering temperature is remarkably reduced by about 150 DEG C, volatilization of Bi in BFO-based ceramic is reduced to the maximum extent, the compactness of the ceramic is enhanced, and excellent energy storage performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials and relates to high-entropy energy storage ceramic materials, and specifically to a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, a preparation method thereof, and an application thereof. Background Art

[0002] The rapid development of pulse power systems, new energy vehicles, and smart grids has created an urgent demand for energy storage devices. Dielectric energy storage ceramic capacitors are considered to be key candidates for the next generation of pulse power technology, with ultrafast charge and discharge rates, ultrahigh power density, and excellent thermal stability. However, their relatively low energy storage density compared to batteries and supercapacitors remains a key limitation. Therefore, exploring new ceramic materials with enhanced energy storage density is necessary to advance the application of pulse power. Recoverable energy density (W rec ) dielectric capacitor, calculate the number of cycles by integration Depends on the polarization difference (ΔP = P max -P r ) and breakdown strength (E b ). Therefore, ΔP and E are achieved b The coordinated optimization of the E and P is the key to developing high-performance lead-free energy storage ceramics. Unfortunately, the intrinsic properties of traditional dielectric materials, such as strong hysteresis of ferroelectrics (FE) and antiferroelectrics (AFE), severely limit the realization of large ΔP and energy storage performance. Relaxor ferroelectrics (RFE), characterized by dispersion, diffuse phase transition and thin PE loop, have attracted widespread attention. However, the enhancement of relaxation behavior often leads to the weakening of polarization. How to improve E b Maintaining a moderate ΔP remains a key bottleneck in optimizing RFE energy storage performance.

[0003] In recent years, the unconventional design concept of "high entropy engineering" has become a promising strategy for optimizing the energy storage performance of dielectric ceramics. High entropy materials, characterized by strong intrinsic chemical disorder, severe lattice distortion and complex ion valence states, have shown great potential in adjusting dielectric properties. A large number of studies have focused on adding high entropy materials as relaxant additives to highly polarizable matrices, such as Na 0.5 Bi 0.5 TiO3 (NBT-based), BaTiO3 (BT-based) or BiFeO3 (BF-based system), etc., to induce ionic disorder enhancement and configurational entropy-driven nanoscale polar regions, thereby achieving high ΔP, high energy storage efficiency and excellent dielectric temperature stability. 3+ Similar to Pb 2+ The 6s2 lone pair electron configuration makes BiFeO3-BaTiO3, (Na 0.5 Bi 0.5Bi-based systems such as SrTiO3 have high polarizability. However, the low melting point of Bi2O3 (~800°C) leads to a large amount of Bi volatilization during high-temperature sintering, resulting in high leakage current and low breakdown strength (much lower than SrTiO3 or BaTiO3-based systems). High-entropy strategies alone cannot fully address these limitations. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability and its low-temperature sintering preparation method and application. Through a synergistic optimization strategy combining high entropy engineering with liquid phase sintering, the synergistic enhancement of polarization difference (ΔP) and breakdown strength (Eb) is achieved, and a ceramic material with high breakdown strength, high energy storage density and excellent high-temperature stability is obtained.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A BiFeO3-based high entropy energy storage ceramic material with wide temperature stability, the stoichiometric formula is (1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3, wherein x represents molar percentage, x=0.06~0.15.

[0007] The present invention also protects a BiFeO3-based high entropy energy storage ceramic material with wide temperature stability, the raw materials include (1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 and 0.5-2wt% of BaCu(B2O5), wherein x represents molar percentage, x=0.06-0.15.

[0008] The present invention also protects a method for preparing the BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability as described above, comprising the following steps:

[0009] Step 1: According to (1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2Ca 0.2 )(Ti 0.8 Zr 0.2 ) The raw material ratio of O3 is Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3, which are mixed, ball-milled, dried and then calcined at 800-850°C for 3-5h to obtain powder A;

[0010] Step 2: BaCO3, CuO and H3BO3 are mixed according to the molar ratio of BaCu(B2O5), ball-milled, dried and calcined at 850-900°C for 3-5h to obtain powder B;

[0011] Step 3: Powder A and 0.5-2 wt% of powder B are mixed, ball-milled for a second time, dried, and sieved to obtain a mixed powder. The mixed powder is poured into a mold, pressed into shape, and demolded. The embryo is then obtained by cold isostatic pressing.

[0012] Step 4: Place the green body obtained in step 3 into a muffle furnace, heat it from room temperature to 900-960°C at a rate of 3-5°C / min in an air atmosphere, keep it warm for 2-4 hours, then reduce it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0013] Preferably, the ball milling in step 1 and step 2 is performed by mixing the raw materials, zirconia balls and deionized water in a mass ratio of 1:5:1 and milling for 10 to 12 hours.

[0014] Preferably, the drying in step 1, step 2 and step 3 is performed by placing the product in an oven at 80° C. for 12 to 24 hours.

[0015] Preferably, the secondary ball milling in step 3 is performed by mixing the raw materials, zirconia balls and deionized water in a mass ratio of 1:5:1 and milling for 8 hours.

[0016] Preferably, the sieving in step 3 is through a 120-200 mesh sieve.

[0017] Preferably, the cold isostatic pressing process in step 3 is cold isostatic pressing for 3 minutes at a pressure of 200 MPa.

[0018] The present invention also protects the use of the above-mentioned BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability in dielectric energy storage ceramic capacitors.

[0019] Compared with the prior art, the present invention has the following technical effects:

[0020] The present invention (1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 ceramic material achieves polarization difference (ΔP) and breakdown strength (E b ) synergistically enhanced, a ceramic with high breakdown strength, high energy storage density and excellent high-temperature stability (83-459°C) was obtained. Compared with other Bi-based materials, the temperature variation range is between ±15% and above 400°C, which is expected to be used in practical applications that require high temperature, high pressure and high energy storage at the same time;

[0021] 1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3-0.5~2wt% BaCu(B2O5) ceramic materials were prepared by designing a synergistic optimization strategy combining high entropy engineering with liquid phase sintering. First, a high entropy system was introduced to destroy the long-range ferroelectric order, inducing a nano-polarized region with high polarization response. The freezing temperature was regulated to near room temperature, which is conducive to the transition from non-ergodic state to ergodic state and obtaining a high ΔP. The optimal composition was introduced into a low-melting-point sintering aid (BCB) (melting point 800-850℃), and the grain refinement was obvious (from 3.0 2μm to 0.56μm), which is mainly due to the low melting point of BCB, which is conducive to liquid phase sintering. This process minimizes the volatilization of Bi in BFO-based ceramics. In addition, the liquid phase acts as a diffusion barrier, delays grain boundary migration, and inhibits grain growth. At the same time, the capillary force driven by the liquid phase promotes particle rearrangement, accelerates mass transport, fills pores, and enhances ceramic density (relative density increases from 90% to 95%; Under the synergistic optimization of the two, excellent energy storage performance (7.25J / cm 3 ), solved the problem of Bi volatilization in BFO-based ceramics, achieved densification sintering in the low-temperature range of 900-960°C, which is 150°C lower than traditional sintering. This greatly suppressed the volatilization of Bi in BiFeO3-based ceramics and obtained submicron-scale grains. The submicron-scale grain size (0.57μm) was obtained, and high breakdown strength was achieved without sacrificing polarization, ultimately achieving a significant improvement in energy storage performance; this has not been seen in previous studies;

[0022] The invention has a simple preparation process, low material cost, and is green and environmentally friendly. It is expected to become an important candidate material that is both technically and economically superior to replace lead-based ceramic materials for high-end industrial application materials; it also greatly reduces energy consumption and achieves green development. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Calculation of the tolerance factor and configurational entropy of the NBBSCZ-x high-entropy energy storage ceramics with wide temperature stability prepared in Examples 1-4 and Comparative Example 1 of the present invention (a) and their XRD patterns at room temperature (b, c);

[0024] Figure 2 NBBSCZ-x high-entropy energy storage ceramics with wide temperature stability prepared in Examples 1-4 of the present invention: (a) Temperature dependence of TCC at 150°C; (b) Temperature range of TCC < ±15%; (c) Comparison of temperature dependence of TCC coefficient;

[0025] Figure 3 SEM images (ac) and average grain size and relative density (d) of NBBSCZ-0, NBBSCZ-0.12, and NBBSCZ-0.12-1wt% BCB high-entropy energy storage ceramics with wide temperature stability prepared in Example 3, Example 7, and Comparative Example 1 of the present invention;

[0026] Figure 4 NBBSCZ-0, NBBSCZ-0.12, NBBSCZ-0.12-1wt% BCB high entropy energy storage ceramics with wide temperature stability prepared in Example 3, Example 7 and Comparative Example 1 of the present invention: (a) Unipolar PE loop at room temperature; (b) Corresponding W rec ,W tal and η; (c) main performance parameters (E b ,ΔP,W rec ,W tal ,P max ,P r , and W rec ) comparison; (d) comparison with other lead-free systems;

[0027] Figure 5 NBBSCZ-0.12-1wt% BCB high entropy energy storage ceramics with wide temperature stability prepared in Example 7 of the present invention: (a) Underdamped discharge current curve at 20-120 kV / cm, with I in the inset. max Curves of changes with electric field; (b) C D and P D as a function of the electric field; (e) Time dependence of the overdamped discharge current curve (R = 200Ω); (d) W calculated from the overdamped curve disRelationships that change over time. DETAILED DESCRIPTION

[0028] The specific contents of the present invention are further explained in detail below with reference to the embodiments.

[0029] Example 1

[0030] This embodiment provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0031] Step 1: 0.94(0.67BiFeO3-0.33BaTiO3)-0.06(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the raw materials, zirconia balls and deionized water were ball-milled for 18 hours in a mass ratio of 1:5:1. The mixture was then dried in an oven at 80°C for 24 hours and finally calcined at 850°C for 4 hours to obtain a mixed powder;

[0032] Step 2: The mixed powder was mixed with the raw materials, zirconia balls, and deionized water in a mass ratio of 1:5:1 and ball-milled for a second time for 8 hours. The mixed powder was then placed in an oven and dried at 80°C for 24 hours, then passed through a 200-mesh sieve. The obtained powder was poured into a mold and pressed into shape, then demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 minutes to obtain an embryo;

[0033] Step 3: Place the green body obtained in step 2 into a muffle furnace, heat it from room temperature to 1070°C at a rate of 5°C / min in an air atmosphere, keep it warm for 3 hours, then cool it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0034] Example 2

[0035] This embodiment provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0036] Step 1: 0.91(0.67BiFeO3-0.33BaTiO3)-0.09(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti0.8 Zr 0.2 )O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the raw materials, zirconia balls and deionized water were ball-milled for 18 hours in a mass ratio of 1:5:1. The mixture was then dried in an oven at 80°C for 24 hours and finally calcined at 850°C for 4 hours to obtain a mixed powder;

[0037] Step 2: The mixed powder was mixed with the raw materials, zirconia balls, and deionized water in a mass ratio of 1:5:1 and ball-milled for a second time for 8 hours. The mixed powder was then placed in an oven and dried at 80°C for 24 hours, then passed through a 200-mesh sieve. The obtained powder was poured into a mold and pressed into shape, then demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 minutes to obtain an embryo;

[0038] Step 3: Place the green body obtained in step 2 into a muffle furnace, heat it from room temperature to 1080°C at a rate of 5°C / min in an air atmosphere, keep it warm for 3 hours, then cool it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0039] Example 3

[0040] This embodiment provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0041] Step 1: 0.88(0.67BiFeO3-0.33BaTiO3)-0.12(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the raw materials, zirconia balls and deionized water were ball-milled for 18 hours in a mass ratio of 1:5:1. The mixture was then dried in an oven at 80°C for 24 hours and finally calcined at 850°C for 4 hours to obtain a mixed powder;

[0042] Step 2: The mixed powder was mixed with the raw materials, zirconia balls, and deionized water in a mass ratio of 1:5:1 and ball-milled for a second time for 8 hours. The mixed powder was then placed in an oven and dried at 80°C for 24 hours, then passed through a 200-mesh sieve. The obtained powder was poured into a mold and pressed into shape, then demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 minutes to obtain an embryo;

[0043] Step 3: Place the green body obtained in step 2 into a muffle furnace, heat it from room temperature to 1090°C at a rate of 5°C / min in an air atmosphere, keep it warm for 3 hours, then cool it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0044] Example 4

[0045] This embodiment provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0046] Step 1: 0.85(0.67BiFeO3-0.33BaTiO3)-0.15(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the raw materials, zirconia balls and deionized water were ball-milled for 18 hours in a mass ratio of 1:5:1. The mixture was then dried in an oven at 80°C for 24 hours and finally calcined at 850°C for 4 hours to obtain a mixed powder;

[0047] Step 2: The mixed powder was mixed with the raw materials, zirconia balls, and deionized water in a mass ratio of 1:5:1 and ball-milled for a second time for 8 hours. The mixed powder was then placed in an oven and dried at 80°C for 24 hours, then passed through a 200-mesh sieve. The obtained powder was poured into a mold and pressed into shape, then demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 minutes to obtain an embryo;

[0048] Step 3: Place the green body obtained in step 2 into a muffle furnace, heat it from room temperature to 1100°C at a rate of 5°C / min in an air atmosphere, keep it warm for 3 hours, then reduce it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0049] Example 5

[0050] This embodiment provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0051] Step 1: 0.94(0.67BiFeO3-0.33BaTiO3)-0.06(Na 0.2 Bi 0.2 Ba 0.2 Sr0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the raw materials, zirconia balls and deionized water were ball-milled for 10 hours in a mass ratio of 1:5:1. The mixture was then dried in an oven at 80°C for 12 hours and calcined at 800°C for 5 hours to obtain powder A;

[0052] Step 2: BaCO3, CuO, and H3BO3 were mixed according to the molar ratio of BaCu(B2O5), and the mixture was ball-milled for 10 h according to the mass ratio of raw materials, zirconia balls, and deionized water of 1:5:1. The mixture was then dried in an oven at 80°C for 12 h and calcined at 850°C for 5 h to obtain powder B.

[0053] Step 3: Powder A and 0.5 wt% of powder B were mixed, and the mixture was ball-milled for a second time for 8 h according to the mass ratio of raw materials, zirconia balls, and deionized water of 1:5:1. The mixture was placed in an oven and dried at 80 ° C for 12 h, and then passed through a 120-mesh sieve to obtain a mixed powder. The mixed powder was poured into a mold, pressed into shape, and demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 min to obtain an embryo;

[0054] Step 4: Place the green body obtained in step 3 into a muffle furnace, heat it from room temperature to 960°C at a rate of 3°C / min in an air atmosphere, keep it warm for 2 hours, then reduce it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0055] Example 6

[0056] This embodiment provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0057] Step 1: 0.91(0.67BiFeO3-0.33BaTiO3)-0.09(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2)O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the raw materials, zirconia balls and deionized water were ball-milled for 11 hours in a mass ratio of 1:5:1. The mixture was then dried in an oven at 80°C for 15 hours and calcined at 820°C for 5 hours to obtain powder A;

[0058] Step 2: BaCO3, CuO, and H3BO3 were mixed according to the molar ratio of BaCu(B2O5), and the mixture was ball-milled for 11 hours according to the mass ratio of raw materials, zirconia balls, and deionized water of 1:5:1. The mixture was then dried in an oven at 80°C for 15 hours and calcined at 850-900°C for 4 hours to obtain powder B.

[0059] Step 3: Powder A and 1.5 wt% of powder B were mixed, and the mixture was ball-milled for a second time for 8 h according to the mass ratio of raw materials, zirconia balls, and deionized water of 1:5:1. The mixture was placed in an oven and dried at 80 ° C for 15 h, and then passed through a 150 mesh sieve to obtain a mixed powder. The mixed powder was poured into a mold, pressed into shape, and demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 min to obtain an embryo;

[0060] Step 4: Place the green body obtained in step 3 into a muffle furnace, heat it from room temperature to 950°C at a rate of 4°C / min in an air atmosphere, keep it warm for 4 hours, then cool it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0061] Example 7

[0062] This embodiment provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0063] Step 1: 0.88(0.67BiFeO3-0.33BaTiO3)-0.12(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the raw materials, zirconia balls and deionized water were ball-milled for 12 hours in a mass ratio of 1:5:1. The mixture was then dried in an oven at 80°C for 24 hours and calcined at 850°C for 4 hours to obtain powder A;

[0064] Step two, BaCO3, CuO and H3BO3 are mixed according to the element molar ratio of BaCu(B2O5), ball milling is performed for 12 h according to the mass ratio of raw materials, zirconia balls and deionized water 1:5:1, then drying is performed in an oven at 80℃ for 24 h, calcination is performed at 850-900℃ for 4 h, and powder B is obtained;

[0065] Step three, powder A and 1wt% of powder B are mixed, secondary ball milling is performed for 8 h according to the mass ratio of raw materials, zirconia balls and deionized water 1:5:1, drying is performed in an oven at 80℃ for 24 h, then sieving is performed through a 200 mesh sieve, and mixed powder is obtained, the mixed powder is poured into a mold for compression molding, then demolding is performed, and green body is obtained by cold isostatic pressing under the condition of 200Mpa pressure for 3 min;

[0066] Step four, the green body obtained in step three is placed in a muffle furnace, and sintering is performed by heating from room temperature to 920℃ at a rate of 5℃ / min in an air atmosphere, holding for 3 h, then cooling to 500℃ at a rate of 5℃ / min, and then cooling to room temperature with the furnace, to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0067] Example 8

[0068] The embodiment provides a preparation method of a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0069] Step one, Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 are mixed according to the raw material ratio of 0.85(0.67BiFeO3-0.33BaTiO3)-0.15(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3, ball milling is performed for 10 h according to the mass ratio of raw materials, zirconia balls and deionized water 1:5:1, then drying is performed in an oven at 80℃ for 12-24 h, and calcination is performed at 850℃ for 5 h, to obtain powder A;

[0070] Step two, BaCO3, CuO and H3BO3 are mixed according to the element molar ratio of BaCu(B2O5), ball milling is performed for 12 h according to the mass ratio of raw materials, zirconia balls and deionized water 1:5:1, then drying is performed in an oven at 80℃ for 12 h, calcination is performed at 850-900℃ for 4 h, and powder B is obtained;

[0071] Step 3: Powder A and 2 wt% of powder B were mixed, and the mixture was ball-milled for 8 h according to the mass ratio of raw materials, zirconia balls, and deionized water of 1:5:1. The mixture was placed in an oven and dried at 80 ° C for 12 h, and then passed through a 200 mesh sieve to obtain a mixed powder. The mixed powder was poured into a mold, pressed into shape, and demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 min to obtain an embryo;

[0072] Step 4: Place the green body obtained in step 3 into a muffle furnace, heat it from room temperature to 900°C at a rate of 5°C / min in an air atmosphere, keep it warm for 3 hours, then reduce it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0073] Comparative Example 1

[0074] This comparative example provides a method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, comprising the following steps:

[0075] Step 1: (0.67BiFeO3-0.33BaTiO3)-0(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 raw material ratio: Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3 were mixed, and the mixture was ball-milled for 18 hours according to the mass ratio of raw materials, zirconia balls and deionized water of 1:5:1, and then placed in an oven for drying at 80°C for 24 hours, and finally calcined at 860°C for 4 hours to obtain a mixed powder;

[0076] Step 2: The mixed powder was mixed with the raw materials, zirconia balls, and deionized water in a mass ratio of 1:5:1 and ball-milled for a second time for 8 hours. The mixed powder was then placed in an oven and dried at 80°C for 24 hours, then passed through a 200-mesh sieve. The obtained powder was poured into a mold and pressed into shape, then demolded. The embryo was then cold isostatically pressed at a pressure of 200 MPa for 3 minutes to obtain an embryo;

[0077] Step 3: Place the green body obtained in step 2 into a muffle furnace, heat it from room temperature to 1090°C at a rate of 5°C / min in an air atmosphere, keep it warm for 3 hours, then cool it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

[0078] Figure 1The tolerance factor and configurational entropy as well as the XRD patterns calculated for the NBBSCZ-x high entropy energy storage ceramics prepared in Examples 1-4 and Comparative Example 1. Within the composition range (x = 0.06-0.15), the configurational entropy of NBBSCZ-x ceramics always exceeds 1.61R, which is a high entropy material. The enhanced configurational entropy reduces the Gibbs free energy, thereby improving the thermodynamic stability. This mechanism is conducive to the stability of the single-phase structure and inhibits the formation of secondary phases. In addition, the lattice stability of high-entropy perovskites with single-phase characteristics depends on the tolerance factor (t), and t values ​​below 0.9 or above 1.1 usually correspond to unstable perovskite structures. After the introduction of NBBSCZ, the t value stabilizes near 1 (1.003 to 0.998), which is conducive to the formation of a stable high-entropy perovskite structure ( Figure 1 (a)). The room temperature XRD spectrum of NBBSCZ-x ceramics and the magnified image of the (110) diffraction peak are shown in Figure 2. Figure 1 Previous studies have shown that due to the instability of BiFeO3 itself, Bi2O3 volatilization is easy to occur at high temperatures, which leads to stoichiometric problems and secondary phases (Bi2Fe2O9, Bi 25 FeO 40 However, all NBBSCZ-x high entropy energy storage ceramics in this study exhibited a single perovskite structure, and no secondary phase was detected, confirming that NBBSCZ formed a complete solid solution in the 0.67BFO-0.33BTO system. The suppression of the secondary phase is due to the improved thermodynamic stability of high entropy engineering. In addition, when x increases from 0.06 to 0.15 ( Figure 1 (c)), the (110) diffraction peak gradually shifts to a lower 2θ angle ( Figure 1 (c)), indicating that the smaller Bi 3+ and Fe 3+ Ions are larger (Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 ) 2+ and Zr 4+ Ionic substitution causes lattice expansion.

[0079] Figure 2NBBSCZ-x high-entropy energy storage ceramics prepared for Examples 1-4 of the present invention were compared for temperature dependence of TCC and temperature dependence of TCC coefficient at 150 °C. Fluctuations can cause significant changes in dielectric constant, εr, thereby degrading the capacitance, energy storage efficiency, and reliability of electronic devices. Therefore, improving the temperature stability of dielectric materials, quantified by the temperature coefficient of capacitance (TCC), is a key objective in material design. The results show that NBBSCZ-0.12 and NBBSCZ-0.15 high-entropy energy storage ceramics exhibit excellent dielectric temperature stability (TCC < 15%) over an ultra-wide temperature range of 66-464 °C and 83-459 °C, respectively, as shown in Figure 2 (b). This remarkable stability can be attributed to the enhanced configurational entropy, which helps to promote the formation of dynamic nanodomains. These nanodomains are less sensitive to external temperature fluctuations, suppressing sudden changes in ε r Figure 2 (c). To characterize the temperature stability of NBBSCZ-x (x = 0.12 and 0.15), we compared their TCC values with those recently reported for dielectric materials, including BF-, BT-, and NBT-based systems

[0080] Figure 3 SEM images and average grain size and relative density of NBBSCZ-0, NBBSCZ-0.12, NBBSCZ-0.12-1 wt% BCB high-entropy energy storage ceramics with wide temperature stability prepared for Example 3, Example 7, and Comparative Example 1 of the present invention. Figure 3 (a-c) show the surface morphology of NBBSCZ-0, NBBSCZ-0.12, and NBBSCZ-0.12-1 wt% BCB ceramics, with the insets showing the grain size distribution histograms obtained by Nano Measurement software. Figure 3 ​(d) Comparison of the average grain size and relative density of the three samples. The results show that the grain size of the NBBSCZ-0.12-1wt% BCB high-entropy energy storage ceramic is reduced by more than five times compared to the undoped sample (NBBSCZ-0), reaching the submicron level (0.56μm); the inverse relationship between grain size and breakdown strength explains the improvement in breakdown performance after grain refinement. The main reason for the reduction in grain size in the NBBSCZ-0.12 high-entropy energy storage ceramic is the slow diffusion effect inherent in high-entropy energy storage ceramics. The cooperative diffusion resistance induced by multi-element doping synergistically hinders atomic migration and grain boundary migration, resulting in the gradual refinement of grains with increasing configurational entropy. The addition of BCB leads to significant grain refinement, which is mainly due to the low melting point of BCB (800-850°C), which is conducive to liquid-phase sintering. This process significantly reduces the sintering temperature by 150°C, minimizing the volatilization of Bi in the ceramic. The capillary force driven by the liquid phase promotes particle rearrangement, accelerates mass transport, fills pores, and enhances ceramic density (relative density increases from 90% to 95%).

[0081] Figure 4 The energy storage performance of NBBSCZ-0, NBBSCZ-0.12, and NBBSCZ-0.12-1wt% BCB high entropy energy storage ceramics prepared in Example 3, Example 7, and Comparative Example 1 of the present invention was tested. Figure 4 (a) shows the unipolar PE loops of NBBSCZ-0, NBBSCZ-0.12, and NBBSCZ-0.12-1wt% BCB ceramics at a critical breakdown field of 10 Hz. By integrating the loops, the energy storage density and efficiency can be calculated, as shown in Figure 4 (b) Key performance indicators (E b ,ΔP,W rec ,η,P max and P r ) is a comprehensive comparison of Figure 4 (c) The results show that NBBSCZ-0.12-1wt% BCB high entropy energy storage ceramics have twice the energy storage efficiency and lower P compared to NBBSCZ-0 ceramics. r This resulted in a 4.29-fold increase in overall energy storage performance. Ultimately, superior energy storage performance (W rec =7.25J / cm 3 ). Comparative analysis with recent studies ( Figure 4 (d)) highlights the W of the ceramic protrusion prepared by the present invention rec and E b .

[0082] Figure 5The pulse discharge performance of the NBBSCZ-0.12-1wt% BCB high entropy energy storage ceramic with wide temperature stability prepared in Example 7 of the present invention was tested. The pulse discharge performance of ceramic capacitors is a key factor in evaluating their applicability for practical use. In practical applications, the energy stored in these capacitors needs to be discharged as quickly as possible to achieve high power density. The underdamped discharge behavior of the NBBSCZ-0.12-1wt% BCB high entropy energy storage ceramic was quantified using an RLC resonant circuit ( Figure 5 (a)), thus directly obtaining the target parameters. Figure 5 (b) shows the calculated C D and P D As a function of the electric field, Figure 5 The 90% energy release time (τ 0.9 ) showed that NBBSCZ-0.12-1wt% BCB high entropy energy storage ceramics achieved a nanosecond τ of 51ns 0.9 values, demonstrating excellent pulse discharge performance and ultrafast energy delivery capability, which quickly shows its suitability for real-world high-power applications.

Claims

1. A BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, characterized in that: The stoichiometric formula is (1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3, wherein x represents molar percentage, x=0.06~0.

15.

2. A BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability, characterized in that: The raw materials include (1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 )O3 and 0.5-2wt% of BaCu(B2O5), wherein x represents molar percentage, x=0.06-0.

15.

3. A method for preparing the BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability as claimed in claim 2, characterized in that: The following steps are involved: Step 1: According to (1-x)(0.67BiFeO3-0.33BaTiO3)-x(Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )(Ti 0.8 Zr 0.2 ) The raw material ratio of O3 is Na2CO3, Bi2O3, SrCO3, CaCO3, Fe2O3, TiO2, ZrO2 and BaCO3, which are mixed, ball-milled, dried and then calcined at 800-850°C for 3-5h to obtain powder A; Step 2: BaCO3, CuO and H3BO3 are mixed according to the molar ratio of BaCu(B2O5), ball-milled, dried and calcined at 850-900°C for 3-5h to obtain powder B; Step 3: Powder A and 0.5-2 wt% of powder B are mixed, ball-milled for a second time, dried, and sieved to obtain a mixed powder. The mixed powder is poured into a mold, pressed into shape, and demolded. The embryo is then obtained by cold isostatic pressing. Step 4: Place the green body obtained in step 3 into a muffle furnace, heat it from room temperature to 900-960°C at a rate of 3-5°C / min in an air atmosphere, keep it warm for 2-4 hours, then reduce it to 500°C at a rate of 5°C / min, and then cool it to room temperature and sinter it into porcelain to obtain a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability.

4. The method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability according to claim 3, characterized in that: The ball milling in step 1 and step 2 is performed by mixing the raw materials, zirconia balls and deionized water in a mass ratio of 1:5:1 and milling for 10 to 12 hours.

5. The method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability according to claim 3, characterized in that: The drying in step 1, step 2 and step 3 is carried out by placing the product in an oven at 80° C. for 12 to 24 hours.

6. The method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability according to claim 3, characterized in that: The secondary ball milling in step 3 is performed by mixing the raw materials, zirconia balls and deionized water in a mass ratio of 1:5:1 and milling for 8 hours.

7. The method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability according to claim 3, characterized in that: The sieving in step 3 is through a 120-200 mesh sieve.

8. The method for preparing a BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability according to claim 3, characterized in that: The cold isostatic pressing process described in step 3 is cold isostatic pressing for 3 minutes under a pressure of 200 MPa.

9. Use of the BiFeO3-based high-entropy energy storage ceramic material with wide temperature stability as claimed in claim 1 or 2 in a dielectric energy storage ceramic capacitor.